Strategi Pemasaran Syariah Produk Tabungan Sajada Di BMT NU Cabang Blega Bangkalan: Studi Implementasi - Kulsum, Ummi (Program Studi Perbankan Syariah Institut Al-Fithrah (IAF) Surabaya, 2025)
This study aims to find out what kind of sharia marketing strategy is implemented in SAJADAH savings products at BMT NU Blega Bangkalan Branch. The results of this research are that there are four strategies that have been implemented, namely Gathering directly to customers' homes, Distribution of Brochures, Cooperation with institutions or organizations and marketing through social media. From this, it can be seen that in attracting the interest of customers of BMT NU Blega Bangkalan Branch, it is not only one strategy to attract customers. And of course this is quite effective and efficient. The method used in this research is qualitative descriptive. Qualitative descriptive is data in the form of words, pictures and not numbers. The primary data in this study is an interview with the BMT NU Blega Bangkalan Branch. Meanwhile, the secondary data in this study are brochures, photographs, books, journals and others that can strengthen this research.